2018
DOI: 10.1091/mbc.e18-05-0291
|View full text |Cite
|
Sign up to set email alerts
|

In vivo analysis of outer arm dynein transport reveals cargo-specific intraflagellar transport properties

Abstract: Outer dynein arms (ODAs) are multiprotein complexes that drive flagellar beating. Based on genetic and biochemical analyses, ODAs preassemble in the cell body and then move into the flagellum by intraflagellar transport (IFT). To study ODA transport in vivo, we expressed the essential intermediate chain 2 tagged with mNeonGreen (IC2-NG) to rescue the corresponding Chlamydomonas reinhardtii mutant oda6. IC2-NG moved by IFT; the transport was of low processivity and increased in frequency during flagellar growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 70 publications
1
61
0
Order By: Relevance
“…In many organisms, it is possible to precisely edit (as opposed to disrupt) genes via CRISPR/Cas9-mediated HDR, and there currently is much interest in developing efficient methods for such precise gene editing in C. reinhardtii [e.g., 17,18,20]. However, if one has a C. reinhardtii null mutant, such as those generated by TIM, that mutant usually can be "rescued" by transformation with constructs designed to express the affected protein with engineered changes ranging from a single amino-acid substitution to addition of an affinity or fluorescent tag [e.g., 27,[31][32][33][34][35][36][37][38][39][40]. For non-essential genes, the ease with which this can be accomplished in C. reinhardtii makes this approach a reasonable alternative to precise gene editing by CRISPR/Cas9-mediated HDR.…”
Section: Plos Onementioning
confidence: 99%
“…In many organisms, it is possible to precisely edit (as opposed to disrupt) genes via CRISPR/Cas9-mediated HDR, and there currently is much interest in developing efficient methods for such precise gene editing in C. reinhardtii [e.g., 17,18,20]. However, if one has a C. reinhardtii null mutant, such as those generated by TIM, that mutant usually can be "rescued" by transformation with constructs designed to express the affected protein with engineered changes ranging from a single amino-acid substitution to addition of an affinity or fluorescent tag [e.g., 27,[31][32][33][34][35][36][37][38][39][40]. For non-essential genes, the ease with which this can be accomplished in C. reinhardtii makes this approach a reasonable alternative to precise gene editing by CRISPR/Cas9-mediated HDR.…”
Section: Plos Onementioning
confidence: 99%
“…Proteins that contain WD-repeat domains (i.e., WD40 or beta-transducin repeat domain superfamily proteins) are known to serve as hubs for protein interactions in a variety of cellular processes, including signal transduction, RNA synthesis, RNA processing, chromatin assembly, and apoptosis (Li & Roberts, 2001;Stirnimann, Petsalaki, Russell, & Muller, 2010). DAW1 serves as a hub for interactions that promote loading of outer dynein arms on ciliary axonemes (Ahmed et al, 2008;Dai, Barbieri, Mitchell, & Lechtreck, 2018;Taschner et al, 2017), which is required for proper motile cilia function in algae, fish, and mice (Ahmed & Mitchell, 2005;Gao et al, 2010;Li et al, 2015). The abnormalities in planarian motility, epidermal ciliary beating, and protonephridia function observed upon Smed-daw1 RNAi in planarians, support the notion that DAW1 serves a conserved role in promoting the loading of dynein arms into axonemes of motile cilia in the Platyhelminthes.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas Plass et al (2018) reported expression of Smed-daw1 in GABAergic and cholinergic neurons. The ortholog of IFT46, which is the intraflagellar transport protein that works with DAW1 to deliver dynein arms to axonemes (Ahmed et al, 2008;Dai et al, 2018;Hou & Witman, 2017;Taschner et al, 2017), displays a similar pattern of expression in planarian cells, with enrichment in GABAergic and cholinergic neurons (Plass et al, 2018). Although the neuronal expression of Smed-daw1 was not validated functionally or by in situ hybridization, it is worth considering possible contributions of DAW1 in cells that (as far as we know) may not have motile cilia.…”
Section: Discussionmentioning
confidence: 99%
“…For all experiments, Chlamydomonas cells were suspended in a HEPES/NMG buffer consisting of 5 mM HEPES, 1 mM KCl, 1 mM HCl, 500 µM CaCl2, 200 µM EGTA (free Ca 2+ 301 µM) and pH adjusted to 7.4 with N-methyl-D-glucamine [6]. To remove external Ca 2+ , cells were perfused with a Ca 2+ -free buffer in which CaCl2 had been omitted.…”
Section: Tirf Imaging Of Flagellamentioning
confidence: 99%
“…IFT particles are composed of around 20 proteins arranged into two sub-complexes (IFT-A and IFT-B). Proteins within the IFT-B complex have specific roles in binding to cargo proteins including important structural components such as such as tubulin (IFT74/81) and outer arm dynein (IFT46) 5,6 . IFT-A proteins interact with cargo proteins involved in signalling pathways, such as Gprotein coupled receptors 7 .…”
Section: Introductionmentioning
confidence: 99%